Automated registration of multi-view point clouds using sphere targets. Issue 4 (October 2015) - Yun, Dongho; Kim, Sunghan; Heo, Heeyoung; Ko, Kwang Hee
Highlights: Methods of detecting sphere targets using geometric properties are presented. A procedure for fine registration of point-clouds using targets is presented. A new system for point-cloud registration is developed and demonstrated. Abstract: This paper addresses the problem of automated registration of multi-view point clouds generated by a 3D scanner using sphere targets. First, sphere targets are detected from each point cloud. The centroids of the detected targets in each point cloud are then used for rough registration. Congruent triangles are computed from the centroids for the correspondence among them, with which a rigid body transformation is obtained to bring the two point clouds together as closely as possible. After the initial registration, the two point clouds are further registered by refining the position and orientation of the point clouds using the underlying geometric shapes of the targets. These registration steps are integrated into one system that allows two input point clouds automatically registered with no user intervention. Real examples are used to demonstrate the performance of the point cloud registration.